(untitled) (Asian Journal of Medical and Biological Research, 2022)
The general aim of orthodontic treatment is to provide ideal occlusion, facial aesthetics and stability in individuals, as well as to provide healthy periodontal structures. A good orthodontic treatment can be possible with healthy gingiva. Plaque accumulation may occur in the tooth areas around the equipment used in orthodontic appliances. The microbiological composition of dental plaque is related to dental and oral health. During the orthodontic treatment process, microbiological changes may occur in the flora. Therefore, before starting orthodontic treatment, the oral hygiene of the patient should be checked. It should be considered that the lack of oral hygiene may cause complications. In this review, information on the relationship between orthodontic treatment and oral flora is summarized. Asian J. Med. Biol. Res. 2022, 8 (4), 181-186